Identifying emotional and psychological abuse : a guide for childcare professionals - O'Hagan, Kieran (Open University Press, 2006)
The principal objectives of this book are to enable childcare workers to understand and deal more effectively with cases of emotional and psychological abuse. The concepts of emotional development, emotional abuse, psychological development, and psychological abuse are fully explored and clearly defined, within the contexts of: existing literature and research; childcare legislation and practice; child abuse enquiry reports, and, in particular that of Victoria Climbie. The book identifies emotional and psychological development and abuse in specific age categories, 0-4, 5-12, and adolescence. Case studies and vignettes are used to highlight normal development and abusive situations. Comprehensive frameworks which are easily applicable to current practice, are provided, enabling workers to observe and accurately assess the quality of emotional and psychological life of children. "Identifying Emotional and Psychological Abuse" is key reading for health and social care professionals, as well as students with an interest in child protection